The Pengaruh Status Gizi Terhadap Prestasi Akademik SMA Ignatius Slamet Riyadi Cijantung: Hubungan Status Gizi dengan Prestasi Akademik Siswa/i SMA Ignatius Slamet Riyadi Cijantung - Pancarani, Dini Angela; Karjadidjaja, Idawati (Jurnal MedScientiae, 2025)
Nutrition is one of the factors that determine the quality of human being. If the intake of nutritious food is lacking or excessive, especially in children and adolescents, it will result in health problems that will lead to low academic achievement and reduce the quality of human being. This study aims to determine the relationship between nutritional status and academic achievement of Ignatius Slamet Riyadi High School students, Cijantung. This research is an analytic-observational study with a cross-sectional design with a sample size of 194 students. This study was conducted on students of Ignatius Slamet Riyadi High School, Cijantung, grades X to XII in January 2025. The data collected consisted of taking the weight and height of students and filling out questionnaires about factors that affect nutritional status with academic achievement in the form of average report card scores in the previous semester. Calculation of nutritional status using the CDC 2000 growth chart. It was found that students who had normal nutritional status and had good academic achievement were 67 people (88.2%) while those who had abnormal nutritional status and had fair academic achievement were 22 people (18.6%).Test analysis of the relationship between variables using Fisher's Exact Test obtained (p > 0,288) and PRR value = 1.574. From the results of this study, there was no significant relationship between nutritional status and academic performance in Ignatius Slamet Riyadi Cijantung High School students